Studi Hadis dalam Perspektif Sosial - Bustamin Bustamin (Refleksi: Jurnal Kajian Agama dan Filsafat, 2007)
This writing is based on the generalization of understanding towards hadith. It means that all hadiths are understood in the same way without distinguishing the structure of the hadith, whether it is transmitted by wording or meaning (riwayat bi al-lafzh or riwayat bi al-ma’na), the absolute or relative field of the hadith’s content (related to creed and worship) or relative (related to transactions). Hadiths are often only understood with textual interpretation techniques, with only a small portion expanding them with contextual interpretation techniques, both historical and sociological contexts, as an idea. In this context, the understanding of the Prophet’s hadith needs to consider several things, including Prophet Muhammad as the source of information, the companions as recipients of information, the form and scope of the meaning of the Prophet’s hadith, events surrounding the emergence of the Prophet’s hadith, and the social and community conditions that occurred at that time.